Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Ask your questions and receive precise answers from experienced professionals across different disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Question 3 of 10

Given the functions:

[tex]\[
\begin{array}{l}
f(x) = x + 4 \\
g(x) = 3x^2 - 7
\end{array}
\][/tex]

Find [tex]\((f \cdot g)(x)\)[/tex]

A. [tex]\((f \cdot g)(x) = 3x^3 + 12x^2 + 7x + 28\)[/tex]
B. [tex]\((f \cdot g)(x) = 3x^3 + 12x^2 - 7x - 28\)[/tex]
C. [tex]\((f \cdot g)(x) = 3x^3 - 28\)[/tex]
D. [tex]\((f \cdot g)(x) = 3x^3 + 28\)[/tex]


Sagot :

To find [tex]\((f \cdot g)(x)\)[/tex], we need to multiply the two given functions [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] together.

Given:
[tex]\[ f(x) = x + 4 \][/tex]
[tex]\[ g(x) = 3x^2 - 7 \][/tex]

First, we multiply these functions together:
[tex]\[ (f \cdot g)(x) = f(x) \cdot g(x) = (x + 4)(3x^2 - 7) \][/tex]

Now, we need to expand this product step-by-step:

1. Distribute [tex]\( x \)[/tex] across [tex]\( 3x^2 - 7 \)[/tex]:
[tex]\[ x \cdot (3x^2 - 7) = 3x^3 - 7x \][/tex]

2. Distribute [tex]\( 4 \)[/tex] across [tex]\( 3x^2 - 7 \)[/tex]:
[tex]\[ 4 \cdot (3x^2 - 7) = 12x^2 - 28 \][/tex]

3. Combine these results:
[tex]\[ (x + 4)(3x^2 - 7) = 3x^3 - 7x + 12x^2 - 28 \][/tex]

Next, we write it in standard polynomial order, combining like terms where applicable:
[tex]\[ (f \cdot g)(x) = 3x^3 + 12x^2 - 7x - 28 \][/tex]

Thus, the expanded form of [tex]\( (f \cdot g)(x) \)[/tex] is:
[tex]\[ 3x^3 + 12x^2 - 7x - 28 \][/tex]

So, the correct answer is:
[tex]\[ B. \ (f \cdot g)(x) = 3x^3 + 12x^2 - 7x - 28 \][/tex]